PENGARUH KONSENTRASI H2SO4 PADA PERLAKUAN AWAL DAN WAKTU FERMENTASI TERHADAP KADAR BIOETANOL YANG DIHASILKAN - Euis Kusniawati (Politeknik Akamigas Palembang, 2015)
Rice straw as agriculture waste has the potential to be used as raw material for alternative energy, namely bioethanol or other alternative fuels. Rice straw contains cellulose and hemicellulose that can be used to produce ethanol by hydrolysis and fermentation. The rice straw was pretreated by alkaline and acid pretreatment. Then, pretreated rice straw was hydrolyzed enzymatically and fermented to produce bioethanol. The results showed that the biggest ethanol obtained was 2,699% at 3 days of fermentation time and acid concentrations pretreatment of 5%.